Structural determinants of customer loyalty among long-term insurance consumers in Namibia - Bianca Tjizumaue; Sulaiman Olusegun Atiku (Cogent Business & Management, 2024)
Customer satisfaction, retention, and loyalty are essential for a positive return on sales in the insurance industry. This study examines the key determinants of customer loyalty among long‑term insurance consumers in Namibia. The mediating role of customer satisfaction was also examined in the relationship between the specified exogenous variables and customer loyalty. A quantitative approach was adopted using a cross‑sectional survey to establish the structural determinants of loyalty among long‑term insurance consumers in Namibia. An explanatory research design was incorporated to explain the mediating role of customer satisfaction in the relationship between customer awareness and customer loyalty, customer protection and customer loyalty, as well as service quality and customer loyalty in Namibia. The target population (18,205) of this study comprised consumers of long‑term insurance products in Windhoek, Namibia. A structured questionnaire was administered to 406 respondents using a convenience sampling technique. The formulated hypotheses were assessed using variance‑based structural equation modeling. The results show that customer satisfaction exerts a direct effect on customer loyalty, while customer protection and service quality exert an indirect influence on customer loyalty in the insurance industry. Therefore, efforts should be geared towards customer awareness of long‑term insurance products to enhance the uptake of such products for customer satisfaction and customer loyalty in the insurance industry.
Keywords: 650; Customer awareness; customer loyalty; customer protection; customer satisfaction; service quality